Juridical Review On The Instructions Of Governor Of Yogyakarta No. K/898/I/1975 On Uniformity Policy Of Land To The Granting Of A Non-Native Citizen - Frans Ferbianto; Umar Ma'ruf (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2018)
The purpose of this study was to: 1) To determine and analyze the implementation of The Instruction of DIY No. K/898/I/1975 which makes it difficult to obtain a non-native citizen property rights of land in Yogyakarta. 2) To determine and analyze the correlation instructions for DIY Regional Head No. K/898/I/1975 with other legal regulations. The data used in this study are primary data, secondary data and data that can support tertiary study, which was then analyzed by descriptive analytical method. Based on the results of data analysis concluded that: 1) The provision granting land rights to a citizen Non-Natives in the province based instructions for DIY Regional Head No. K/898/I/A/1975 are not allowed to own land both farm and nonagricultural land with soil status Rights Owned. If a citizen Non Natives acquire land with the right then obliged to waive that right and land rights apply to the Regional Head of DIY with a given the building right (HGB). 2) The provision granting land rights to a Non-Native citizen in the province based instructions for DIY Regional Head No. K/898/I/1975.Keywords: Judicial Review; Non-Native Citizen; Rights of Land